Developing A Rapid Transfer from Opioid Full Agonist to Buprenorphine: "Ultrarapid Micro-Dosing" Proof of Concept. Issue 1 (1st January 2023) - Azar, Pouya; Mathew, Nickie; Mahal, Daljeet; Wong, James S.H.; Westenberg, Jean N.; Schütz, Christian G.; Greenwald, Mark K.
ABSTRACT: Buprenorphine/naloxone has been shown to be effective for treating opioid use disorder (OUD). However, the traditional method of induction requires a patient to be in moderate-to-severe withdrawal, which is challenging, time-consuming, and a common reason for leaving against medical advice. Induction strategies that minimize the severity and duration of patient discomfort while enabling patients to reach therapeutic doses during short hospital admissions can mitigate difficulties when inducing a patient on buprenorphine/naloxone. This case-series illustrates two patients with OUD using illicit fentanyl, who were successfully started on buprenorphine/naloxone using 24-hour and 6-hour micro-dosing induction protocol. During induction, the patients were up-titrated to a therapeutic dose through ultrarapid micro-dosing with ongoing use of short-acting opioids. Both patients reached therapeutic doses experiencing minimal levels of withdrawal. This case-series is a proof of concept for the use of a buprenorphine/naloxone ultrarapid micro-induction protocol for inpatients with OUD. By reducing the length of induction and precluding the need for withdrawal, this method offers several advantages over previously published inductions protocols and can improve the accessibility of buprenorphine/naloxone to patients with OUD.